HUBUNGAN SUPERVISI PENGAJARAN DAN KOMITMEN DENGAN KINERJA GURU - Kurilah Kurilah (UNIVERSITAS BENGKULU, 2019)
This research described whether there is a significant correlation between teaching supervision, commitment to teachers’ performance in Public Elementary School in Ketahun District North Bengkulu. The research methods of this study was descriptive quantitative and the techniques of data collection is questionare. The research subjects were teachers. The findings of this study show that to get a significant correlation between teaching supervision to teachers’ performance which obtained partial correlation coefficient of 0.840 (84%), to get the correlation between commitment to teachers’ performance which obtained partial correlation coefficient of 0,564 (56,4%), and to get the correlation between teaching supervision, commitment to teachers’ performance which obtained double correlation coefficient of 0,871 (87,1%).